2005
DOI: 10.1007/s10755-005-6300-9
|View full text |Cite
|
Sign up to set email alerts
|

Research Circles: Supporting the Scholarship of Junior Faculty

Abstract: This article describes and assesses "Research Circles" as a mechanism for enhancing faculty collegiality and research. Recently established on our campus, these circles, composed of three to four faculty members, have had a particularly powerful effect on the new faculty members' adjustment to their tenure track positions, especially since they entered a context that might otherwise have been challenging: a new interdisciplinary upper-division campus with high expectations for teaching excellence. Based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 2 publications
1
15
0
4
Order By: Relevance
“…They also may not have a good understanding of each journal's audience or trends. These combined difficulties result in publications from junior researchers typically taking a fair amount of years to first appear (Gillespie et al, 2005).…”
Section: Prior Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They also may not have a good understanding of each journal's audience or trends. These combined difficulties result in publications from junior researchers typically taking a fair amount of years to first appear (Gillespie et al, 2005).…”
Section: Prior Workmentioning
confidence: 99%
“…Pese a haber adquirido un considerable dominio de un tópico de investigación dado, su falta de experiencia escribiendo en un género discursivo particular (el formato artículo de investigación), sumado al hecho de quizás no conocer bien las audiencias y/o tendencias de cada revista, hacen que las primeras publicaciones de los investigadores noveles suelan tardar un buen número de años en aparecer (Gillespie et al, 2005).…”
Section: Antecedentesunclassified
“…Los Ciclos de Mejora aparecen como una herramienta alternativa para la formación (Gillespie, Dolˇsak, Kochis, Krabill, Lerum, Peterson & Thomas, 2005), que favorece el desarrollo profesional y la construcción de la identidad del profesorado novel universitario; permitiendo que éste sea capaz de enfrentarse a situaciones diversas. Estos ciclos de supervisión clínica se entienden como metodologías activas de formación, recomendadas para el desarrollo de competencias de los profesionales (Arribas, Carabias & Monreal, 2010).…”
Section: Metodologíaunclassified
“…One strategy for ensuring that time set aside for research is actually spent on research would be to cultivate a system of accountability, such as research circles or readings groups (Carroll 2003;Gillespie et al 2005). Specifically, Carroll (2003) suggested that these groups "can provide the deadlines and immediate feedback that many faculty need for completing projects and exposing their work to a higher level of scrutiny" (p. 26).…”
Section: Researchmentioning
confidence: 99%